Triangular hysteresis loops in the spin-rotation region of orthoferrites - Bazaliy, Ya.B.; Tsymbal, L.T. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Suggested theory qualitatively explains the shapes of the hysteresis loops in orthoferrites within the temperature interval of the magnetic reorientation transition. Triangular loops result from the strong temperature dependence of both the magnetic moment and the magnetic domain wall structure.